2016
DOI: 10.3892/ijmm.2016.2644
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of ILK attenuates the abnormal proliferation and migration of human Tenon's capsule fibroblasts induced by TGF-β2

Abstract: The cytokine, transforming growth factor-β (TGF-β), plays a key role in wound healing and tissue repair. Integrin-linked kinase (ILK) is a downstream factor of the TGF-β signaling pathway. Research on ILK has mainly focused on its role in the invasion and metastasis of cancer cells. However, little has been reported on the effects of ILK in human Tenon's capsule fibroblasts (HTFs). In this study, we investigated the role of ILK in the proliferation and migration of HTFs exposed to TGF-β2. A lentiviral vector t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Blocking PDGFC has been reported to reduce the growth and angiogenesis of tumors that are resistant to anti-VEGF therapies [ 32 , 33 , 34 ]. The ILK gene, a downstream target of TFG-β, was also reduced by DMS-EVs ( Figure 5 b); interestingly, studies have shown that silencing ILK inhibits cancer cells stimulated by TFG-β2 [ 35 ]. AKT1 was also downregulated by 1 and 10 µg/mL of DMS-EVs ( Figure 5 b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking PDGFC has been reported to reduce the growth and angiogenesis of tumors that are resistant to anti-VEGF therapies [ 32 , 33 , 34 ]. The ILK gene, a downstream target of TFG-β, was also reduced by DMS-EVs ( Figure 5 b); interestingly, studies have shown that silencing ILK inhibits cancer cells stimulated by TFG-β2 [ 35 ]. AKT1 was also downregulated by 1 and 10 µg/mL of DMS-EVs ( Figure 5 b).…”
Section: Resultsmentioning
confidence: 99%
“…CD44, a cell surface adhesion receptor that mediates cell–ECM interactions, can activate various signaling pathways that lead to cell proliferation, migration, and invasion. Studies have shown that knocking out CD44 suppresses the EMT phenotype ( Figure 5 c) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…30 Additionally, knockout of ILK decreased the invasion and metastasis abilities of cells through inhibiting the EMT process. 31 , 32 Considering the crucial roles of EMT in modulating cell migration and invasion, ILK may be a promising treatment target for various diseases. Tang et al discovered that emodin inhibited the expression of ILK through the crosstalk of AMPKα and ERK1/2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin-linked kinase ( ILK ) is a serine/threonine protein kinase located in focal adhesions, which promotes cell growth, proliferation, differentiation, migration and invasion [15]. ILK expression and activity have been revealed to be increased in association with the tumor grade, T status, lymph node metastasis and survival rate of lung cancer patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of ILK has also been discovered to facilitate glioma cell invasion and migration and down-regulate E-cadherin. Besides, the inhibition of ILK has been shown to lead to cell cycle stagnation and stimulate apoptosis in PTEN-negative prostate cancer cells [15]. Indeed, previous studies have demonstrated that the increased ILK expression in poorly differentiated thyroid cancer and confirmed the relationship between ILK overexpression and poor prognosis [17].…”
Section: Introductionmentioning
confidence: 99%